Gambaran Budaya Keselamatan Pasien di Rumah Sakit : Studi Kasus pada Area Manajemen Pelayanan - Alfid Tri Afandi; Anggun Dyah Pramita; Kholid Rosyidi Muhammad Nur; Yudho Tri Handoko (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Patient safety is a system that makes patient care safer, including risk assessment, identification of patient risk management, reporting and analysis of incidents, the ability to learn from incidents and their follow-up, and implementation of solutions to minimize risks and prevent injuries caused by errors. as a result of carrying out an action or not taking the action that should be taken. The hospital inpatient room is devoted to services for patients requiring more handling related to patient safety measures. This case study aims to find out the description of patient safety culture in hospital inpatient rooms. This case study uses a sample of 16 nurses in the inpatient ward, and the instrument used is the Hospital Survey of Patient Safety Culture Version 2.0, translated into Indonesian. It consists of 42 questions in 5 parts. The questionnaire results describe positive or negative values. This shows that in all aspects of the questionnaire, indicators > 70%, namely positive responses including the work unit section 70%, your supervisor 73.45%, the communication section 97.93, the incident frequency report section 91.7%, and the natural hospital section promotes patient safety 78.42%. The results of each indicator show that the picture of patient safety culture in the Hospital Inpatient Room is good, with a positive response of 85.25%. This research hopes to improve performance in patient safety culture as a health service provider